2017
DOI: 10.1073/pnas.1620813114
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of autoregulatory scaffolding by apoptosis signal-regulating kinase 1

Abstract: Apoptosis signal-regulating kinases (ASK1-3) are apical kinases of the p38 and JNK MAP kinase pathways. They are activated by diverse stress stimuli, including reactive oxygen species, cytokines, and osmotic stress; however, a molecular understanding of how ASK proteins are controlled remains obscure. Here, we report a biochemical analysis of the ASK1 kinase domain in conjunction with its N-terminal thioredoxin-binding domain, along with a central regulatory region that links the two. We show that in solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 79 publications
0
48
1
Order By: Relevance
“…In fact, crosstalk between GIT1 and ASK1 signaling has not yet been reported. As the major apical kinase of the p38 and JNK signaling pathway (13,57), ASK1 plays key roles in the regulation of neuronal death by I/R injury (14)(15)(16)(17). Either excess or inadequate activation of ASK1 can disrupt homeostasis and lead to pathologic consequences, which indicates that keeping normal ASK1 activity is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, crosstalk between GIT1 and ASK1 signaling has not yet been reported. As the major apical kinase of the p38 and JNK signaling pathway (13,57), ASK1 plays key roles in the regulation of neuronal death by I/R injury (14)(15)(16)(17). Either excess or inadequate activation of ASK1 can disrupt homeostasis and lead to pathologic consequences, which indicates that keeping normal ASK1 activity is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that TRAF2 and 6 induce an open conformation of the CRR and enable homo‐oligomerization of the N‐terminal part of ASK1, thereby promoting autophosphorylation of the activation loop and binding of downstream MAP2Ks . In turn, other studies have proposed that TRX controls ASK1 function through redox state‐dependent interactions because the oxidized form of TRX, with disulfide‐linked catalytic cysteines C32 and C35, and the TRX C32,35S mutant exhibit considerably weaker binding affinities for ASK1 .…”
Section: Introductionmentioning
confidence: 99%
“…With growing knowledge of the domain structures of ASK kinases the obvious challenge is understanding how oligomerisation by the SAM at the C-terminus integrates with the raft of other interactions through their N-termini. Previously, we reported the crystal structure of the central regulatory region of ASK1-found N-terminal to the kinase domain-which links the N-terminal thioredoxin-binding domain to the kinase domain (18). A pleckstrin-homology domain within this novel fold appears to promote substrate MAP2K phosphorylation, which could occur on an intra-or inter-molecular basis.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear if regulation of substrate recruitment and priming, through a domain just Nterminal to the kinase (18), occur in an intra-or inter-molecular manner. Likewise it is not known if dimers reported for the isolated kinase domain of ASK1 impact kinase function in the context of full-length protein (16).…”
Section: Introductionmentioning
confidence: 99%